Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0162632
|View full text |Cite
|
Sign up to set email alerts
|

Lebetin 2, a Snake Venom-Derived Natriuretic Peptide, Attenuates Acute Myocardial Ischemic Injury through the Modulation of Mitochondrial Permeability Transition Pore at the Time of Reperfusion

Abstract: Cardiac ischemia is one of the leading causes of death worldwide. It is now well established that natriuretic peptides can attenuate the development of irreversible ischemic injury during myocardial infarction. Lebetin 2 (L2) is a new discovered peptide isolated from Macrovipera lebetina venom with structural similarity to B-type natriuretic peptide (BNP). Our objectives were to define the acute cardioprotective actions of L2 in isolated Langendorff-perfused rat hearts after regional or global ischemia-reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 73 publications
(108 reference statements)
2
21
0
Order By: Relevance
“…However, lebetin 2 was found to be more potent than BNP in enhancing the coronary flow, improving contractile dysfunction of myocardium and surviving global IR. It was also suggested that L2 could be a strong drug candidate for acute myocardial ischemia [ 151 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…However, lebetin 2 was found to be more potent than BNP in enhancing the coronary flow, improving contractile dysfunction of myocardium and surviving global IR. It was also suggested that L2 could be a strong drug candidate for acute myocardial ischemia [ 151 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…Isatin also inhibited ANP-induced relaxation of isolated rabbit carotid arteries [110], partially inhibited CNP-stimulated cGMP production by human corneal epithelium [111], and blocked intracellular calcium transient induced by BNP in cardiac sympathetic neurons [112]. Isatin completely blocked the ANP effect on hyperpolarizationactivated current in human atrial myocytes [113] and decreased changes in intracellular calcium of cardiac sympathetic neurons induced by BNP [114]. Since the effect of isatin was similar to that of a cGMP protein kinase inhibitor, RP-8-Br-PET-cGMP, it was concluded that BNP acted via the NPR-A-cGMP-PKG pathway [112].…”
Section: Isatin As a Npr Antagonistmentioning
confidence: 99%
“…Interestingly, isatin acted as an antagonist not only of naturally occurring natriuretic peptides but also of Lebetin 2 (L2); this recently discovered peptide isolated from Macrovipera lebetina venom shares structural similarity to the B‐type natriuretic peptide (BNP) . Isatin blocked cardioprotection by Lebetin 2 in Langendorff‐perfused rat hearts exposed to regional or global ischemia‐reperfusion .…”
Section: Isatin As a Npr Antagonistmentioning
confidence: 99%
“…Lebetin 2 (L2) has been recently found in Macrovipera lebetina venom. This peptide shows structural similarity to B-type natriuretic peptide (BNP), a cardioprotective hormone, and, therefore, displays cardioprotective properties by stimulating natriuretic peptide receptors in ischemia-reperfusion injuries in isolated Langendorff-perfused rat hearts [ 87 ].…”
Section: Macrovipera Lebetinamentioning
confidence: 99%